(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
New tellurated schiff bases were synthesized by the reaction of the corresponding mercurated Schiff Â bases compounds A1-A3 with tellurium tetrabromide in 1:1 mole ratio and Â that Â gave organyltellurium tribromides Â A4-A6. Â On the other hand, when mercurated schiff bases and tellurium tetrabromide brought Â together in 2:1 mole ratio gave diorganyltellurium dibromides compounds A10-A12 followed by reduction with hydrazine hydrate gave new diorganyl tellurides A13-A15.Â Reduction of compounds A4-A6 byÂ hydrazine hydrate gave new ditellurides A7-A9. Â All compounds were characterized by elemental analysis, IR, 1H , 13C NMR, HSQC-NMR and mass spectra.Â Invitro anti-tumor bioactivity of some compounds were tested.Â